2020
DOI: 10.1136/bmjgh-2019-002223
|View full text |Cite
|
Sign up to set email alerts
|

Engaging men to transform inequitable gender attitudes and prevent intimate partner violence: a cluster randomised controlled trial in North and South Kivu, Democratic Republic of Congo

Abstract: IntroductionThe study objective was to understand the effectiveness of Engaging Men through Accountable Practice (EMAP), a group-based discussion series which sought to transform gender relations in communities, on intimate partner violence (IPV), gender inequitable attitudes and related outcomes.MethodsA two-armed, matched-pair, cluster randomised controlled trial was conducted between 2016 and 2018 in eastern Democratic Republic of Congo. Adult men (n=1387) and their female partners (n=1220) participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…Social desirability bias is a widely acknowledged limitation of existing scholarship on men's support for WE (Charles, 2019;Lawoko, 2008;Levtov et al, 2014;Schuler et al, 2011;Vaillant et al, 2020), and evidenced by common results such being interviewed by a woman rather than a man increasing the likelihood of endorsing gender equality (Charles, 2019). It may also make sense of some surprising findings.…”
Section: Hypothesesmentioning
confidence: 99%
“…Social desirability bias is a widely acknowledged limitation of existing scholarship on men's support for WE (Charles, 2019;Lawoko, 2008;Levtov et al, 2014;Schuler et al, 2011;Vaillant et al, 2020), and evidenced by common results such being interviewed by a woman rather than a man increasing the likelihood of endorsing gender equality (Charles, 2019). It may also make sense of some surprising findings.…”
Section: Hypothesesmentioning
confidence: 99%
“…Videos approx. 20 min long with group session x 60 min Qualitative- Interview + FGDs Hossain et al [ 51 ] Cote d'Ivoire Social norms IPV − Men -community members (15 yrs +) Men & Women in Partnership initiative − Weekly male discussion group sessions × 16 compared to community-level programming for raised awareness on women’s rights and GBV impacts CRCT Hossain et al [ 39 ] Kenya Survivor response + community mobilisation IPV − Women refugees (15 yrs +) after IPV/SV Case management + psychosocial support + GBV messaging Mixed Methods Koegler et al [ 47 ] DRC Economic empowerment SV − Women − survivors of conflict-related SV Group credit and animal asset transfer; shared farming; weekly group support meetings − Solidarity Groups 1–2 h Qualitative − Interview Lilleston et al [ 54 ] Lebanon Survivor response + community mobilisation SV + IPV − Refugee women and adolescent girls GBV mobile service delivery approach − 6 months of weekly individual case management; psychosocial support; information sessions; door-to-door visits Qualitative − Interview Stark et al [ 55 ] Ethiopia Empowerment + relationship skills SV + IPV − Girls (13–19 yrs) and their mothers COMPASS − 30 life skills sessions × 1–3 h + 8 mothers’ sessions (length not reported) compared to wait list CRCT Stark et al [ 56 ] DRC Empowerment + relationship skills SV + IPV − Girls (10–14 yrs) and their mothers COMPASS − 32 life skills sessions × 1-3 h + 13 mothers sessions (length not reported) compared to wait list CRCT Vaillant [ 50 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 summarises the evidence for reduced risk and changed incidence of intimate partner violence and/or sexual violence as well as the key impacts of the interventions. Four studies identified reductions in incidence of intimate partner violence [ 40 , 46 , 49 , 50 ] and one of sexual and intimate partner violence [ 51 ], though none reached statistical significance. One showed reduced intimate partner violence only among a sub-set of women with moderate baseline food insecurity [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…To address rigidly entrenched gender norms, especially within short time-spans, it is therefore important that men be involved to harness their support of women's empowerment. A trial in Rwanda (Dunkle et al 2020) and research in the Democratic Republic of Congo (Vaillant et al 2020), alongside other evidence (Armenti and Babcock 2016;Stern, McGhee, et al 2020) have shown that when men and women are involved as couples, there is a significant reduction of intimate partner violence, including sexual intimate partner violence, as well as economic and psychological empowerment of women. There needs to be recognition however that some men may not be interested in participating in such programmes or that there may be a 'backlash' towards them, if men do not view the intervention as helpful.…”
Section: Discussionmentioning
confidence: 99%